Focus on Empowering Rural Women and Improving Commercial Small-scale Subsistence Agriculture to Alleviate Poverty in Rural Papua New Guinea - Nasi, Philip (International Journal of Social Sciences and Humanities, 2023)
Majority of indigenous people of Papua New Guinea live on subsistence farming practices to provide for their families. The research shows that women in rural areas play a paramount role through subsistence agriculture in sustaining livelihood. The subsistence agriculture has long been practiced in Papua New Guinea since prehistory and the women play key roles in selling surplus farm produces at local markets.